PV-WT Based Distribution Generator Location Minimizing Transmission Loss in Pool/Bilateral Electricity Market Model. (2016) - Kumar, Manish; Kumar, Ashwani; Sandhu, K.S.
Abstract: In this paper, analysis has been carried out for transmission loss minimization with the integrated hybrid PV and Wind turbine in the power system network. For obtaining the power output from the PV and Wind turbine, a probabilistic model for the solar irradiation and wind has been considering using Beta and Weibull distribution function. A Mixed Integer Nonlinear Programming (MINLP) approach has been utilized for determining optimal location and number of distributed generators considering minimization of transmission loss. The analysis has been carried out with constant PQ load and Zip load model. The impact of different load models has been studied. The analysis has been carried out for IEEE24 bus test system in pool/bilateral electricity market model.